The Role of Corporate Image, Quality Service and Customer Satisfaction To Intention Behavior and Customer Loyalty - Ardhana, Nugroho Aji; Mariam, Siti; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to investigate the relationship between corporate image, service quality, customer satisfaction, behavioral intention, and customer loyalty at PT Indomarco Prismatama ( Indomaret ). The research utilizes a quantitative approach with a descriptive design, involving 155 respondents selected through purposive sampling. Data were collected using an online questionnaire and analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM). The findings indicate that corporate image positively and significantly influences customer satisfaction, which in turn influences behavioral intention and customer loyalty. Additionally, service quality is shown to positively impact both corporate image and customer satisfaction. Validity and reliability tests confirm that all variables in the model exhibit good quality. The study supports all proposed hypotheses and is consistent with previous research, highlighting the importance of corporate image, service quality, and customer satisfaction in influencing behavioral intention and customer loyalty. Managerial implications include the need to focus on enhancing service quality and strengthening corporate image to increase customer satisfaction and loyalty. Limitations of the study include the restricted sample scope to the Jabodetabek area and the use of online data collection methods. Future research is recommended to expand the sample scope and consider longitudinal approaches. Keywords: Corporate Image, Service Quality, Customer Satisfaction, Behavioral Intention, Customer Loyalty.